Provocation tests in doppler ultrasonography for carpal tunnel syndrome - Ng, Esther S.; Ng, Kay W.; Wilder-Smith, Einar (Muscle & nerve, 2013)
Introduction: Doppler ultrasonography (DU) has recently been shown to be useful in imaging carpal tunnel syndrome (CTS). In this study, we aim to characterize the changes seen after exercise and electrical stimulation. Methods: Five patients with CTS were recruited with 5 age-matched subjects. DU was used to visualize the median nerve, flexor tendon, and bone at base line and after 1 minute of: (a) median nerve motor stimulation, (b) median nerve sensory stimulation, (c) abductor pollicis brevis contraction, and (d) adductor digiti minimi contraction. Results: Blood flow in the median nerve was greater after APB exercise. Furthermore, blood flow in the median nerve was greater in cases than controls after APB exercise. At baseline, blood flow in the flexor tendon was greater in cases than controls. Conclusions: While limited by sample size, this study demonstrates that exercise of median innervated muscles may be useful in enhancing diagnostic utility of DU for CTS. Muscle Nerve, 2013